Frissito Helse Cafe / Mohamed Azeem Mohamed Joeharry ... [et al.] - Mohamed Joeharry, Mohamed Azeem; Abdul Latip, Nooraihan; Abd Kadir, Mohd Faqhrull Shafiq; Andres Pacana, Noor Dyana; Juli, Nursafika Bahira (2015)
Frissito Helse Cafe is a company that operates here in Tanjung Aru, Sabah that offers its customers healthy food and beverages. The word "Frissito" was taken from Hungarian word meaning "Refreshing" while the word "Helse" is a Norwegian word that means "Health". When combine together it will give a meaning of "Refreshing Health Cafe" for our company's name. The name itself will give our customers a little idea of what to expect from our cafe. In our cafe, we sell healthy food such as steamed chicken with brown rice, whole wheat bread with honey and toppings, fruit salads, fruit popsicles and fruit juices. Our main target is to attract and encourage people to try healthy food in order to start a healthy lifestyle. With the cafe located at Tanjung Aru Beach, tourist and also locals will be our target market. A total of seven workers work in our cafe which is a waiter, a promoter that also acts a part time waiter, general, admin, marketing, operation and financial manager. We start the business with financial aid which was obtained from both bank loans and equity. It is essential for all entrepreneur to prepare a business plan when opening a new business. It will be a guideline and reference not only for the entrepreneur themselves, but also to banks, suppliers and customers. In this business plan, we have present every important aspect in chapters for the convenience of readers. Nonetheless, we hope that this business will make us as a successful entrepreneur.